Anticancer Potential of Doxorubicin in Combination with Green-Synthesized Silver Nanoparticle and its Cytotoxicity Effects on Cardio-Myoblast Normal Cells - Saeidi, Jafar; Dolatabadi, Samaneh; Esfahani, Mahbubeh B.; Saeidi, Masood; Mohtashami, Mahnaz; Mokhtari, Kiana; Ghasemi, Ahmad (Anti-Cancer Agents in Medicinal Chemistry, 2021)
Background: The use of DOX as an anticancer agent is associated with serious side effects on normal cells especially in cardiovascular tissue. Objective: Here, it is proposed that the combination of a low dose of DOX with AgNPs provides ideal cytotoxicity against cancer cells and decreases side effects on normal human cells. This study evaluates the cytotoxic effects of green-synthetized AgNPs (GS-AgNPs) in combination with DOX in cancerous cells (MCF7) and investigates its influences on cell growth and apoptosis in a normal cell line of the heart (H9c2). Methods: We used coffee extracts, as a reducing and stabilizing agent for the green-synthesis of AgNPs. GSAgNPs were characterized by using various analytical methods. MTT assay was used for cell toxicity analysis in cancerous and normal cells. Moreover, Annexin-V /PI staining and mRNA expression of Bax, Bcl2 and p53 were performed for apoptosis measurement in heart normal cell line. Results: GS-AgNPs showed more biocompatibility for normal cells and higher cytotoxicity for cancerous cells compared to that reported for chemically synthesized nanoparticles. Our results also demonstrated that a selected combination of DOX and AgNPs, 20 μM AgNPs / 0.3 μM DOX, had a suitable cytotoxic effect against cancerous cells with a minimum toxic effect on normal cells. So, no significant alteration was observed in cell migration capacity, apoptosis and gene expression of BAX, Bcl-2 and P53 when H9c2 cells were treated with 20 μM AgNPs / 0.3 μM DOX relative to the non-treated control. Conclusion: Finally, it seems that the combination of GS-AgNPs and DOX could be a potent strategy to combat cancer.
Keywords: doxorubicin